Structure-function Relationships in Serpins: Current Concepts and Controversies - Gils, Ann; Declerck, Paul J. (Thrombosis and Haemostasis, 1998)
Almost two decades ago, a new superfamily of proteins was proposed, based on the similarity between the primary structure of ovalbumin, α1-antitrypsin (also known as α1-proteinase inhibitor) and antithrombin III (1). Even though the acronym “serpins” (serine proteinase inhibitors) was given to these proteins (2), it became soon apparent that a variety of non-inhibitory serpins [e.g. ovalbumin (3), maspin (4), pigment epithelium-derived factor (5)] as well as serpins that inhibit cysteine proteinases [e.g. interleukin-1 β converting enzyme inhibitor (6), cathepsin L inhibitor (7)] belong to this superfamily. Serpins represent about 10% of the total protein in plasma. From these serpins, α1-proteinase inhibitor represents 70%. A number of serpins play a critical role in the regulation of important physiological processes such as blood coagulation (e.g. antithrombin III), fibrinolysis (e.g. plasminogen activator inhibitor 1, PAI-1), complement activation (e.g. C1-inhibitor), and inflammation (e.g. α1-antichymotrypsin) (8) (Table 1). The serpins comprise more than 40 proteins identified from viruses, plants, insects and animals but not from prokaryotes (9). All serpins consist of about 400 residues with molecular masses in the range of 38 to 70 kDa (dependent on the degree of glycosylation) and an overall amino acid homology of approximately 35% (10). Huber and Carrell (10) reported that the conserved residues are localized either internal or in niches on the surface.All serpins have the same highly ordered tertiary structure consisting of 3 β-pleated sheets A, B and C, α-helices A through I and a reactive site loop containing residues P16 to P10’ (10, 11) (Fig. 1). The reactive site, designated P1P1’ and comprising the bait peptide bond, is located within this loop structure situated 30-40 amino acids from the carboxy-terminal end. Using the nomenclature of Schechter and Berger (13), the residues N-terminal to the scissile bond are designated the P-residues (P16 up to P1) whereas the residues to the C-terminal end are designated the P’-residues (P1’ up to P10’) (Table 2).Even though almost all serpins contain Cys residues, only few of them (α2-antiplasmin, C1-inhibitor and antithrombin III) harbor disulfide bridges (10). For α2-antiplasmin it was recently shown that abolishing the disulfide bridge does not influence the thermodynamic stability, the inhibitory activity and the clearance by the receptors (14). Even though reduction of one of the three antithrombin III disulfide bonds does not affect the rate of thrombin inhibition as such, it does abolish the heparin-induced acceleration of the thrombin-antithrombin III interaction (15). These findings suggest that under certain conditions disulfide bridges may play a role in the functional properties of a serpin.